Drink wise, age well; reducing alcohol related harm among people over 50: a study protocol - J. L. Seddon; S. Wadd; E. Wells; L. Elliott; I. Madoc-Jones; J. Breslin (BMC, 2019)
Abstract Background Evidence suggests that the use of alcohol among older adults (defined as those aged 50+) has increased in recent years, with people aged 55-64 now more likely to exceed the recommended weekly guidelines than any other age group. Methods/ design This is a quasi-experimental study with a before-after design. A postal questionnaire will be sent to 76,000 people aged 50 and over registered with a general practice in five different 'demonstration' (intervention) and control areas in the UK. Multiple interventions will then be delivered in demonstration areas across the UK. At the end of the programme, a postal questionnaire will be sent to the same individuals who completed it pre-programme to establish if there has been a reduction in alcohol use, at-risk drinking and alcohol related problems. Qualitative interviews with clients and staff will explore how the interventions were experienced; how they may work to bring about change and to identify areas for practice improvements. Discussion This study protocol describes a multi-level, multi-intervention prevention-to-treatment programme which aims to reduce alcohol-related harm in people aged 50 and over.